Design and Synthesis of Crosslinked Helix Dimers as Protein Tertiary Structure Mimics. Issue 1 (4th January 2022) - Hong, Seong Ho; Nguyen, Thu; Arora, Paramjit
Abstract: Crosslinked helix dimers (CHDs) are synthetic tertiary helical structure motifs designed to modulate interactions of proteins with binding partners. Helix dimers serve as mimics of coiled coils, which are known to be implicated in a multitude of protein complexes. Coiled coils are typically stable in long peptides (>21‐28 residues), because sufficient intra‐ and interstrand contacts are not available in short peptides to coax strand assembly. To engineer conformationally stable CHDs in short sequences, we introduced a covalent linkage in place of an interhelical salt bridge and sculpted the helical interface with optimal hydrophobic packing. CHDs have shown efficacy for the disruption of targeted protein‐protein interactions in biochemical, cellular, and animal models. This article describes our optimized approach to design and synthesize parallel and antiparallel helical tertiary structure mimics. Synthesis of CHDs involves conjugation of individual peptide segments, purification of the mono‐conjugated strand, and alkylation of the two independent strands to yield crosslinked dimers. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Protocol for bis‐triazole CHDs Basic Protocol 2 : Protocol for dibenzyl ether CHDs